Comparison of Mitochondrial Superoxide Detection Ex Vivo/In Vivo by mitoSOX HPLC Method with Classical Assays in Three Different Animal Models of Oxidative Stress - Sanela Kalinovic; Matthias Oelze; Swenja Kröller-Schön; Sebastian Steven; Ksenija Vujacic-Mirski; Miroslava Kvandová; Isabella Schmal; Ahmad Al Zuabi; Thomas Münzel; Andreas Daiber (MDPI AG, 2019)
Background: Reactive oxygen and nitrogen species (RONS such as H2O2, nitric oxide) are generated within the organism. Whereas physiological formation rates confer redox regulation of essential cellular functions and provide the basis for adaptive stress responses, their excessive formation contributes to impaired cellular function or even cell death, organ dysfunction and severe disease phenotypes of the entire organism. Therefore, quantification of RONS formation and knowledge of their tissue/cell/compartment-specific distribution is of great biological and clinical importance. Methods: Here, we used a high-performance/pressure liquid chromatography (HPLC) assay to quantify the superoxide-specific oxidation product of the mitochondria-targeted fluorescence dye triphenylphosphonium-linked hydroethidium (mitoSOX) in biochemical systems and three animal models with established oxidative stress. Type 1 diabetes (single injection of streptozotocin), hypertension (infusion of angiotensin-II for 7 days) and nitrate tolerance (infusion of nitroglycerin for 4 days) was induced in male Wistar rats. Results: The usefulness of mitoSOX/HPLC for quantification of mitochondrial superoxide was confirmed by xanthine oxidase activity as well as isolated stimulated rat heart mitochondria in the presence or absence of superoxide scavengers. Vascular function was assessed by isometric tension methodology and was impaired in the rat models of oxidative stress. Vascular dysfunction correlated with increased mitoSOX oxidation but also classical RONS detection assays as well as typical markers of oxidative stress. Conclusion: mitoSOX/HPLC represents a valid method for detection of mitochondrial superoxide formation in tissues of different animal disease models and correlates well with functional parameters and other markers of oxidative stress.